The collection of the Herpetological Museum of the University of Antioquia (northwestern Colombia) (2015)
ABSTRACT: Northwestern South America harbors one of the richest herpetofauna in the world. The connection among several biogeographic provinces along with climatic and orographic complexity makes this region an important contributor to the Neotropical biodiversity. Despite of this importance, the amphibian and reptile fauna in this area remains largely unknown as few herpetological collections has been made in recent decades. Motivated by this, the Herpetological Museum at the Universidad de Antioquia (Medellín, Colombia) has been increasing the collection in the last 16 years to better understand the herpetofaunal diversity and thus contribute to ecological, systematic, biogeographic and conservation research in the Neotropics. Here, we present the results of this effort and highlight how future collection will impact our understanding of the Neotropical herpetofauna.